Base‐Initiated Formation of FeI–PNP Pincer Complexes. Issue 11 (23rd October 2019) - Glatz, Mathias; Stöger, Berthold; Bichler, Bernhard; Bauer, Gerald; Veiros, Luis F.; Pignitter, Marc; Kirchner, Karl
Abstract : Fe(I) PNP pincer complexes of the type [Fe(PNP NH )(CO)2 ] + were prepared by treatment of the Fe(II) complexes [Fe(PNP NH )(CO)(Cl)2 ] with KO t Bu in an aprotic solvent. The outcome of these reactions is independent of whether it is carried out under a CO atmosphere or not. The tert ‐butyl analog [Fe(PNP NH ‐ t Bu)(CO)2 ]Cl was obtained in a similar fashion but with [Fe(PNP NH ‐ t Bu)(Cl)2 ] as starting material in the presence of CO. In all these reactions the formation of free PNP ligand together with unknown Fe(III) species is presumably due to a 2Fe II → Fe I and Fe III disproportionation process. The cationic complexes could be deprotonated upon treatment with KO t Bu affording the neutral complexes [Fe(PNP N )(CO)2 ]. All compounds are low‐spin complexes as established by their solution effective magnetic moments, X‐band EPR spectra as well as DFT calculations. The solid‐state structures of two representative cationic and neutral complexes, respectively, were determined by single‐crystal X‐ray diffraction. Abstract : Fe(I) PNP pincer complexes of the type [Fe(PNP NH )(CO)2 ] + were prepared from Fe(II) complexes of the type [Fe(PNP NH )(CO)(Cl)2 ] and KO t Bu in an aprotic solvent. In these reactions, the formation of free PNP ligand together with unknown Fe(III) species is observed due to a disproportionation process of the type 2Fe II → Fe I and Fe III .